Viral diversity of Rhipicephalus microplus parasitizing cattle in southern Brazil - William Marciel de Souza; Marcílio Jorge Fumagalli; Adriano de Oliveira Torres Carrasco; Marília Farignoli Romeiro; Sejal Modha; Meire Christina Seki; Janaína Menegazzo Gheller; Sirlei Daffre; Márcio Roberto Teixeira Nunes; Pablo R. Murcia; Gustavo Olszanski Acrani; Luiz Tadeu Moraes Figueiredo (2018)
Ticks are ectoparasites spread worldwide and are well known as vectors of many viruses of great importance to human and animal health. However, the viral diversity in ticks is still poorly understood, particularly in South America. Here we characterized the viral diversity present in Rhipicephalus microplus parasitizing cattle in the southern region of Brazil using metagenomics. Our study revealed the presence of viruses that had not been previously described in the region, including lihan tick virus (Phenuiviridae family) and wuhan tick virus 2 (Chuviridae family), as well as expands the biogeography of jingmen tick virus (Flaviviridae family) in Brazil. Also, we described three novel tymoviruses (Tymovirales order), named guarapuava tymovirus-like 1 to 3. We described the genomic and phylogenetic characterization of these viruses. Our study sheds light on the viral diversity of Rhipicephalus microplus in South America, and also expands the biogeography of tick viruses that were previously described only in Asia.